TRANSFORMATION PROCESSES IN MILITARY TEXTS (SCIENCE TIME JOURNAL, 2025)
This article explores the dynamic nature of military texts, focusing on how they evolve in response to changing contexts, technologies, and communication practices. The author examines various transformation processes, including linguistic shifts, changes in genre conventions, and the impact of digital media on military communication. Key themes include the adaptation of military language to enhance clarity and effectiveness, the role of narrative in shaping military identity, and the influence of social media on public perceptions of military operations.